Human Factors in Digitization Selection of Archival Collection - Nadiah Athirah Abdul Rajah, Nur; Ahmad, Azree; Azli Bunawan, AP; Nurul Emyliana Nik Ramlee, Nik; Hanis Kamarudin, Nurul; Farik Mat Yatin, Saiful; Abdul Malek Wan Abdullah, Wan (International Journal of Engineering and Technology, 2018)
Some records will be kept for a year as it has enduring value that shows evidence from previous business transaction or evidence from the pass event. It will select for permanent preservation called archival collection. In order to preserve the archival collection for future use that might be precious to some organization, digitization is the best solution that can be taken. As to digitize archival collection for public access, some sort of criteria need to be considered. This article discussed on human factors that may affect the selection of archival collection for digitization project.Â Â